Proteomic analysis highlights the role of detoxification pathways in increased tolerance to Huanglongbing disease. Issue 1 (December 2016) - Martinelli, Federico; Reagan, Russell; Dolan, David; Fileccia, Veronica; Dandekar, Abhaya
Abstract Background Huanglongbing (HLB) disease is still the greatest threat to citriculture worldwide. Although there is not any resistance source in theCitrus germplasm, a certain level of moderated tolerance is present. A large-scale analysis of proteomic responses ofCitrus may help: 1) clarifying physiological and molecular effects of disease progression, 2) validating previous data at transcriptomic level, and 3) identifying biomarkers for development of early diagnostics, short-term therapeutics and long-term genetic resistance. Results In this work we have conducted a proteomic analysis of mature leaves of twoCitrus genotypes with well-known differing tolerances to HLB: Navel orange (highly susceptible) and Volkameriana (moderately tolerant). Pathway enrichment analysis showed that amino acid degradation processes occurred to a larger degree in the Navel orange. No clear differences between the two genotypes were observed for primary metabolic pathways. The most important finding was that four glutathione-S-transferases were upregulated in Volkameriana and not in Navel orange. These proteins are involved in radical ion detoxification. Conclusions Upregulation of proteins involved in radical ion detoxification should be considered as an important mechanism of increased tolerance to HLB.